1989
DOI: 10.1007/bf00117715
|View full text |Cite
|
Sign up to set email alerts
|

The study of teachers' written feedback to students' writing: changes in theoretical considerations and the expansion of research contexts

Abstract: This paper identifies four successive phases in the study of written feedback to students' compositions. The studies included in these phases are distinguished by views of writing instruction reflected in their theoretical frameworks: the view of writing instruction as a series of teacher provided stimuli and students' responses to these stimuli; the view that the writing class is a rhetorical community, where teacher and students interact as readers and writers over texts; the view of learning to write as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 33 publications
0
21
0
3
Order By: Relevance
“…Furthermore, some studies have shown written feedback to be one of the least useful strategies for improving student writing (Freedman 1987;Zellermayer 1989). However, the written feedback in this study was appreciated by students for its persistence value as well as for the teaching of essay-writing skills and factual content.…”
Section: Feedback Issuesmentioning
confidence: 72%
“…Furthermore, some studies have shown written feedback to be one of the least useful strategies for improving student writing (Freedman 1987;Zellermayer 1989). However, the written feedback in this study was appreciated by students for its persistence value as well as for the teaching of essay-writing skills and factual content.…”
Section: Feedback Issuesmentioning
confidence: 72%
“…Past studies have consistently focused on the impact of feedback on the learning and performance of the writers who receive that feedback (e.g. Kulik and Kulik 1988) and on the reactions of those writers to that feedback (Coleman et al 1991;Zellermayer 1989). Recent comprehensive reviews have examined feedback in general (Kluger and DeNisi 1996), in education (Hattie and Timperley 2007) and in writing research (Beach and Friedrich 2006;Graham and Perin 2007).…”
Section: Introductionmentioning
confidence: 97%
“…This means that verbal feedback can be provided more readily and there is evidence (e.g., Boulet et al, 1990) that oral feedback may be more effective than written comments. Written feedback on homework or tests seems, however, often to be brief and ineffective; school students have been found to pay little attention to teachers' written comments (Zellermayer, 1989), or find them difficult to interpret and act upon (Clarke, 2000).…”
Section: Individual Versus Whole-class Formative Assessmentmentioning
confidence: 98%